STUDI PENGGUNAAN MANIPULATOR TEGANGAN PADA SENSOR TEKANAN BAHAN BAKAR MESIN DIESEL COMMON RAIL DITINJAU DARI DAYA & KONSUMSI BAHAN BAKAR - Farida, Nike Nur; Monasari, Ratna; Gunawan, Chandra; Aji, Supa K. (Universitas Negeri Surabaya, 2024)
In a common rail diesel engine system, the entire fuel system is regulated electronically by a computer device called the ECU. With this sensor manipulator tool, it is hoped that you will be able to change the output of the fuel pressure sensor to modify the ECU input. This makes it possible to change the power produced by the vehicle and reduce fuel consumption. This research is using experimental methods. The initial step is to take vehicle power test data under normal conditions, with the fuel pressure sensor output voltage at 1.28 V, reduced by 0.2 (1.08 volts), decreased by 0.1 (1.18 volts), increased by 0,1 (1.38 volts), and up 0.2 (1.48 volts). The results of this research show that the highest power at a speed of 80 km/h occurs at a voltage of 1.38 volts and 1.48 volts, with a power of 103 HP. Optimal fuel pressure produces good misting, ensures the mixture of fuel and air in the combustion chamber is homogeneous, and produces maximum power. The results of the fuel consumption test show that the lowest fuel consumption occurs at a vehicle speed of 40 km/hour with a fuel pressure sensor voltage of 1.38 volts, which is around 0.615 cc/second. It can be concluded that a voltage of 1.38 volts produces the most optimal fuel pressure. The throttle valve and pedal openings are still slightly open, so the amount of fuel entering the combustion chamber is also limited, so fuel consumption is very economical.